Association of smoking status with outcomes in hospitalised patients with COVID-19. Issue 1 (5th October 2020) - Adrish, Muhammad; Chilimuri, Sridhar; Mantri, Nikhitha; Sun, Haozhe; Zahid, Maleeha; Gongati, Sudharsan; Fortuzi, Ked; Jog, Abhishrut Pramod; Purmessur, Pravish; Singhal, Ravish
Abstract : Introduction: Smoking causes inflammation of the lung epithelium by releasing cytokines and impairing mucociliary clearance. Some studies have linked smoking with severity of illness of COVID-19 whereas others have found no such association. Methods: This was a retrospective analysis of all adults hospitalised with COVID-19 from 9 March to 18 May 2020. Results: 1173 patients met the study criteria. 837 patients never smoked whereas 336 patients were either current smokers or past smoker and were grouped together in smokers group. Patients in smokers group were more likely to be male and had higher incidence of underlying chronic obstructive pulmonary disease (19% vs 6%, p<0.001), HIV infection (11% vs 5%, p<0.001), cancer (11% vs 6%, p=0.005), congestive heart failure (15% vs 8%, p<0.001), coronary artery disease (15% vs 9%, p=0.3), chronic kidney disease (11% vs 8%, p=0.037) and end-stage renal disease (10% vs 6%, p=0.009) compared with non-smokers. Outcome analysis showed that smokers were more likely to develop critical illness requiring mechanical ventilation (47% vs 37% p=0.005). Univariate Cox model for survival analysis by smoking status showed that among smokers only current smokers had higher risk of death compared with never smokers (HR 1.61, 95% CI 1.22 to 2.12, p<0.001). In the multivariate approach, Cox model for the survival, female sex, young age, low serum lactate dehydrogenase and systemic steroid use were associated with overall improved survival. Conclusion: In our large single-centre retrospective database of patients hospitalised with COVID-19, smoking was associated with development of critical illness and higher likelihood of death.